2015
DOI: 10.1259/bjr.20140712
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic body radiotherapy (SBRT) in the management of extracranial oligometastatic (OM) disease

Abstract: Objective: A review of stereotactic body radiotherapy (SBRT) for oligometastases defined as three or fewer sites of isolated metastatic disease. The aim was to identify local control, overall survival (OS) and progression-free survival (PFS) of patients receiving SBRT for oligometastatic (OM) disease. Methods: Data were analysed for SBRT delivered between 01 September 2010 and 31 March 2014. End points included local control, PFS, OS and toxicity. Results: 76 patients received SBRT. The median age was 60 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Localized therapies including surgery and SBRT are radical treatment options to achieve control of metastatic sites. One recent study 21 of SBRT for oligometastases reported that local control rates was 84.4%, the overall survival (OS) was 84.4% at 1 y and 63.2% at 2 y. A partial response was observed in our case with local Cyberknife therapy and patient is still followed by our group closely.…”
Section: Discussionsupporting
confidence: 51%
“…Localized therapies including surgery and SBRT are radical treatment options to achieve control of metastatic sites. One recent study 21 of SBRT for oligometastases reported that local control rates was 84.4%, the overall survival (OS) was 84.4% at 1 y and 63.2% at 2 y. A partial response was observed in our case with local Cyberknife therapy and patient is still followed by our group closely.…”
Section: Discussionsupporting
confidence: 51%
“…treatment fractions. 35 The a-emitter radionuclide radium-223 has been shown to prolong survival compared with the best supportive care (14.9 vs 11.3 months; HR, 0.70; p 5 0.002) in patients with metastatic castrate-resistant CaP. 36 This systemic treatment is administered intravenously, accumulating at sites of bony metastatic disease and delivering highly damaging lowrange a particles to these sites.…”
Section: Current State Of the Art In Prostate Cancer Diagnosis And Trmentioning
confidence: 99%
“…Antioxidants include glutathione (GSH), thioredoxin (Trx), and melatonin. Antioxidant enzymes include superoxide dismutase (SOD), glutathione peroxidase (GPx), glutathione reductase (GR), catalase (CAT), and heme oxygenase (HO) (Castro and Freeman 2001;Bhattacharya et al 2015). Among the major antioxidant mechanisms, Keap1-NRF2 is a major modulator of cytoprotective reactions against oxidation and stress and one of the core signaling proteins; it is a combination of NRF2 and Keap1, transcription factors that combine with antioxidant response element (ARE) along with small Maf protein.…”
Section: Introductionmentioning
confidence: 99%